2015
DOI: 10.1007/s00167-015-3830-2
|View full text |Cite
|
Sign up to set email alerts
|

Timing of anterior cruciate ligament reconstruction within the first year after trauma and its influence on treatment of cartilage and meniscus pathology

Abstract: Prospective cross-sectional cohort study, Level II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
88
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(99 citation statements)
references
References 45 publications
8
88
1
2
Order By: Relevance
“…The cartilage lesions did not show any differences in treatment at these time points. In contrast, it was found that meniscus injuries associated with ACL reconstruction could be better reconstructed if the surgery was performed in the course of the first 6 months after trauma (77.2% reconstructions of medial menisci within the first 6 months as opposed to 46.1% medial meniscus suturing in the months 7–12 after injury) (Krutsch et al, 2017 ). These results were confirmed by a further study.…”
Section: Reviewmentioning
confidence: 99%
“…The cartilage lesions did not show any differences in treatment at these time points. In contrast, it was found that meniscus injuries associated with ACL reconstruction could be better reconstructed if the surgery was performed in the course of the first 6 months after trauma (77.2% reconstructions of medial menisci within the first 6 months as opposed to 46.1% medial meniscus suturing in the months 7–12 after injury) (Krutsch et al, 2017 ). These results were confirmed by a further study.…”
Section: Reviewmentioning
confidence: 99%
“…Early surgery (<3 week) has shown higher incidences of postoperative stiffness and a fixed flexion deformity with higher rates of manipulation under general anesthesia as compared to delayed repair. 5 20 21 22 …”
Section: Resultsmentioning
confidence: 99%
“…Among these factors, timing of surgical treatment after ACL injury is still controversial (Krutsch et al 2015; Kwok et al 2013). In this study, we divided patients into two groups according to the preoperative periods of 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review classified the injury-to-surgery interval as either early (ranging from within 2 days to 7 months) or delayed (ranging from 3 weeks to 24 years) and found that 8 articles recommended early reconstruction, whereas the majority of the literature found no difference in outcome between early and delayed surgery (Andernord et al 2013). These indicate that the effect of the timing of surgery after injury is still controversy (Krutsch et al 2015; Kwok et al 2013). …”
Section: Introductionmentioning
confidence: 99%